The Status of Interventional Radiology as a Specialty among Medical Students in India—Knowledge, Interest, and Exposure - Sebastian, Bibin; Keshava, Shyamkumar N.; Lakshminarayan, Raghuram (Indian Journal of Radiology and Imaging, 2021)
Purpose Interventional radiology (IR) is a young medical specialty where image guidance is utilized in minimally invasive procedures as a treatment option and/or as a diagnostic tool. There is an exponential increase in awareness and interest in IR amongst medical students. This trend is continuing despite lack of proportionate representation of IR in the current medical curriculum. This study aims to understand the exposure to IR as a specialty amongst medical students in India.Materials and Methods Anonymous, voluntary, online questionnaire was sent to medical students from different parts of the country. The survey comprised 15 questions regarding exposure and awareness on IR.Results The responses were obtained from 1,024 medical students from 98 medical colleges across the country, majority (57.0%) in the clinical years of their training. Thirty-six percent of them were interested in an IR career. Lack of awareness was the most (61.6%) cited reason for not choosing an IR career. Majority (57.9%) would consider IR as a clinical management option and believe that IR holds an important place in medical practice (68.4%).Conclusion There is an evident under-representation of IR in the medical curriculum. However, an increasing awareness and interest among medical students toward IR as a specialty is demonstrated. Incorporation of IR into current medical curriculum in a systematic way is the need of the hour. This would ultimately benefit a wide cohort of patients across multiple specialties.
Keywords: IR; IR curriculum; medical education; medical students; online survey